2017
DOI: 10.1007/s00726-017-2390-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary proteins and amino acids in the control of the muscle mass during immobilization and aging: role of the MPS response

Abstract: Dietary proteins/essential amino acids (EAAs) are nutrients with anabolic properties that may increase muscle mass or attenuate muscle loss during immobilization and aging via the stimulation of muscle protein synthesis (MPS). An EAA's anabolic threshold, capable to maximize the stimulation of MPS has been hypothesized, but during certain conditions associated with muscle loss, this anabolic threshold seems to increase which reduces the efficacy of dietary EAAs to stimulate MPS. Preliminary studies have demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 74 publications
0
28
0
1
Order By: Relevance
“…Even though free Leu supplementation acutely increases muscle protein synthesis, and muscle mass in some long-term studies, other studies have reported no increases in muscle mass following prolonged Leu supplementation [50]. Therefore, it appears that chronically increasing Leu intake via the consumption of an overall increase in dietary protein appears to be the most effective dietary intervention toward increasing or attenuating lean mass during aging.…”
Section: Supplementation With Leumentioning
confidence: 97%
“…Even though free Leu supplementation acutely increases muscle protein synthesis, and muscle mass in some long-term studies, other studies have reported no increases in muscle mass following prolonged Leu supplementation [50]. Therefore, it appears that chronically increasing Leu intake via the consumption of an overall increase in dietary protein appears to be the most effective dietary intervention toward increasing or attenuating lean mass during aging.…”
Section: Supplementation With Leumentioning
confidence: 97%
“…In healthy elderly subjects, the net loss of muscle mass seems to be the result of decreased rates of post-prandial muscle protein synthesis without alterations in the basal muscle protein synthesis (Volpi et al, 2001; D'Antona and Nisoli, 2010; Cholewa et al, 2017; Table 1), whereas in sarcopenic individuals (exhibiting a state of skeletal muscle atrophy), the progression toward sarcopenia ultimately involves alterations in skeletal muscle protein turnover, whereby rates of muscle protein breakdown (MPB) chronically exceed MPS (Trappe et al, 2004; Churchward-Venne et al, 2014). Presently, accurate methodologies have been utilized to measure protein synthesis in vivo , but when measuring protein degradation these methods have presented important limitations, especially when related to MPB (Zanchi et al, 2008).…”
Section: Inflammation Protein Metabolism and Potential Targetsmentioning
confidence: 99%
“…The reason why increased MPB is the major determinant of muscle mass loss during sarcopenia seems to be linked to metabolic/endocrine alterations generated by co-morbidities which accompany sarcopenia. For example, co-morbidities (cancer, sepsis, heart failure) often lead to increased secretion of catabolic hormones such as cortisol, pro-inflammatory molecules such as cytokines, and increased ROS (reactive oxygen species) formation, which may result in increased muscle proteolysis (Crossland et al, 2008, 2010; Brocca et al, 2012; Santilli et al, 2015; Cholewa et al, 2017). …”
Section: Inflammation Protein Metabolism and Potential Targetsmentioning
confidence: 99%
See 2 more Smart Citations